THE FUTURE OF LITERACY: Kick the year off with us by celebrating our 2023 30 Under 30 honorees. - Bothum, Kelly (Literacy Today (2411-7862))
The article announces the International Literacy Association (ILA) 30 Under 30 honorees of 2023 including Shayan Aqdas, Graduate Student, University of Stavanger, Ahmad Siyam Barakati, deputy director, Charmaghz, and Colin Bloom, founder, Libraries for Literacy.